2020
DOI: 10.1038/s41559-020-1166-x
|View full text |Cite
|
Sign up to set email alerts
|

The sterlet sturgeon genome sequence and the mechanisms of segmental rediploidization

Abstract: Sturgeons seem to be frozen in time. The archaic characteristics of this ancient fish lineage place it in a key phylogenetic position at the base of the ~30,000 modern teleost fish species. Moreover, sturgeons are notoriously polyploid, providing unique opportunities to investigate the evolution of polyploid genomes. We assembled a high-quality chromosome-level reference genome for the sterlet, Acipenser ruthenus. Our analysis revealed a very low protein evolution rate that is at least as slow as in other deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
282
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(300 citation statements)
references
References 143 publications
14
282
4
Order By: Relevance
“…In the deeply branched nonteleost ray-finned fishes, the mobilome has been inferred from the genomes of the sturgeon Acipenser ruthenus and the spotted gar, L. oculatus . The former has a similar pattern to that observed in teleosts [ 166 ], while the latter shows a predominance of non-LTR retrotransposons [ 32 , 37 ]. The condition observed in spotted gar is also common to the elephant shark, Callorhinchus milii , and the lamprey, Petromyzon marinus [ 32 ].…”
Section: Transposable Elements In Actinopterygianssupporting
confidence: 55%
“…In the deeply branched nonteleost ray-finned fishes, the mobilome has been inferred from the genomes of the sturgeon Acipenser ruthenus and the spotted gar, L. oculatus . The former has a similar pattern to that observed in teleosts [ 166 ], while the latter shows a predominance of non-LTR retrotransposons [ 32 , 37 ]. The condition observed in spotted gar is also common to the elephant shark, Callorhinchus milii , and the lamprey, Petromyzon marinus [ 32 ].…”
Section: Transposable Elements In Actinopterygianssupporting
confidence: 55%
“…After initial merging and duplication, allopolyploid organisms appear to deduplicate their genomes prominently via fractionation and deletions of orthologs (Yoo et al 2014;Cheng et al 2018;Du et al 2020). However, we found that deletions accounted for a rather minor fraction of restructuration events in polyploid loaches and especially in diploid hybrids.…”
Section: Large-scale Stasis Vs Small-scale Dynamics Of Asexual Genomesmentioning
confidence: 58%
“…For instance, hybrid phenotypes may range from intermediate forms to transgressive expression of novel traits (Bell and Travis 2005;Yoo et al 2014; Bartoš et al 2019); however, often, one parental subgenome is more expressed than the other one, known as expression dominance (Yoo et al 2014;Alexander-Webber et al 2016;Cheng et al 2018). Hybrid and polyploid genomes evolve dynamically and often lose orthologous genes from one or the other parental species in processes referred to as loss of heterozygosity (LOH), genome fractionation, or rediploidization in polyploids (Yoo et al 2014;Lien et al 2016;Du et al 2020). These processes are often considerably asymmetrical (Alexander-Webber et al 2016), and it has been proposed that loss of alleles from the less expressed parental subgenome may cause less severe effects and may, therefore, be preferred by selection (Yoo et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sturgeons and paddlefish comprise 27 living species [32], which branched off 330 Mya [33], from the root of the more than 31,000 living teleosts. The evolutionary history of vertebrates is characterized and embossed by several rounds of whole genome duplications (WGD).…”
Section: Introductionmentioning
confidence: 99%